The Isolation of Specialty Compounds from Amphidinium carterae Biomass by Two-Step Solid-Phase and Liquid-Liquid Extraction - Mercedes López-Rodríguez; Lorenzo López-Rosales; Giulia Diletta Necci; María del Carmen Cerón-García; Elvira Navarro-López; Juan José Gallardo-Rodríguez; Ana Isabel Tristán; Ana Cristina Abreu; Francisco García-Camacho (Toxins, 2022)
The two main methods for partitioning crude methanolic extract from Amphidinium carterae biomass were compared. The objective was to obtain three enriched fractions containing amphidinols (APDs), carotenoids, and fatty acids. Since the most valuable bioproducts are APDs, their recovery was the principal goal. The first method consisted of a solid-phase extraction (SPE) in reverse phase that, for the first time, was optimized to fractionate organic methanolic extracts from Amphidinium carterae biomass using reverse-phase C18 as the adsorbent. The second method consisted of a two-step liquid-liquid extraction coupled with SPE and, alternatively, with solvent partitioning. The SPE method allowed the recovery of the biologically-active fraction (containing the APDs) by eluting with methanol (MeOH): water (H2O) (80:20 v/v). Alternatively, an APD purification strategy using solvent partitioning proved to be a better approach for providing APDs in a clear-cut way. When using n-butanol, APDs were obtained at a 70% concentration (w/w), whereas for the SPE method, the most concentrated fraction was only 18% (w/w). For the other fractions (carotenoids and fatty acids), a two-step liquid-liquid extraction (LLE) method coupled with the solvent partitioning method presented the best results.